2003
DOI: 10.1002/ceat.200303007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Measurement of the Dissolution Rate of Solid Particles in Aqueous Suspensions – Part I: Modeling

Abstract: The dissolution/crystallization rate of suspended particles is a substantial parameter in particle/fluid systems. Frequently, the mass transfer is accompanied by chemical reactions, which affect the mass transfer in the boundary layer surrounding the particles. Additionally, in particular in liquids, the physical interactions between the species dissolved in the suspension have to be considered.In the modeling of such systems one has to differentiate between fast chemical reactions, which instantaneously attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…(5) at a given utilization, the area of limestone particles from each size fraction can be determined by Eqs. (4) and (6), then the dissolution flux of the limestone sample can be calculated by Eq. (3).…”
Section: Dissolution Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) at a given utilization, the area of limestone particles from each size fraction can be determined by Eqs. (4) and (6), then the dissolution flux of the limestone sample can be calculated by Eq. (3).…”
Section: Dissolution Modelmentioning
confidence: 99%
“…Toprac and Rochelle [1] found that there is no effect of limestone type and particle size distribution is the most important influence factor of limestone dissolution. Chan and Rochelle [2], Wallin and Bjerle [3] and Allers et al [4,5] studied the dissolution rate of limestone in a pH-stat apparatus under various conditions and reported that the dissolution process can be successfully simulated by mass transfer model combined with the effects of several equilibrium acid/base reactions and the finite reaction of CO 2 and H 2 O in the boundary layer. Other researchers found that surface reaction may also affect the dissolution process of limestone.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of the particle volume V p is essentially determined by the mole fractions of the calcium ions at the particle surface, x L Ca 2+ can be computed for each particle size from the set of equations of the reaction-diffusion model presented in [2]. Introducing the initial particle volume V 0 , Eq.…”
Section: Adjustment Of the Modelmentioning
confidence: 99%
“…Under the assumption that each particle size distribution is adequately represented by its mean particle size, the monodisperse model presented in [2] was adjusted to these data in the following way.…”
Section: Adjustment Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation